STRATEGY FOR TREATING NATURAL ENVIRONMENT INTO POETRY (INTERPRETATION OF THE ECOPOETRY) - Muakibatul Hasanah; Nita Widiati; Dewi Ariani; Rizka Amaliah (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
The concept of eco-poetic develops in line with changes in the perspective andawareness of poets on the environment. The poet's interaction with nature in thecreative process inspired the selection of learning strategies and learning to writepoetry. This study aims to develop a strategy to use the natural environment as asource of learning to write poetry. The results of the implementation show that thestrategy that departs from natural environment observation activities is effective inwriting natural poetry.